A Re-Appraisal of the Alaskite/Muscovite-Biotite Granite Suite of Halifax County, Nova Scotia - Smith, T.; Peck, D.; Holm, P. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1986)
New mapping, petrography and geochemistry, including REE analyses, indicate that a much larger area of muscovite-biotite granite and fewer alaskite dykes occur in the Halifax - St. Margarets Bay area than was originally thought. The rocks of this area were formed by fractional crystallization of quartz, plagioclase, biotite, zircon, ilmenite, apatite, and monazite. The presence of monazite in the fractional crystallization assenmlage is essential to account tor ttie strong depletion of the rare earth element contents and fractionation of the light rare earth elements noted in these rocks. They have been affected by a pervasive hydrothermal recrystallization and by localized development of pegmatitic vugs and a greisen-bordered sheeted vein complex. A greisen-bordered sheetea vein complex has developed in part of the muscovite-biotite granite south of Sandwich Point, ana although this zone shows all of the features characteristic of the mineralization elsewhere in the batitolith, it is barren.